Pendampingan Edukasi Keuangan Bagi Peserta Didik SMP Muhammadiyah 1 Klaten - Alfiati Nurrokhmini; Arie Rachma Putri; Dea Syiafa Olivia; Dita Nurfika Ayu Saputri (WASATHON Jurnal Pengabdian Masyarakat, 2025)
Financial issues are an important aspect of individual and community life as part of the mechanism for survival. There is still a lack of understanding and knowledge among teenagers, especially students, in managing their personal finances, as well as in organizing themselves and making good financial plans. The preparation stage begins with the service team visiting partners for observation. The service method consists of preparation, implementation, and evaluation stages. The results show a significant increase in students' understanding of good pocket money management, indicating that they now understand the importance of saving. There is also an improvement in their ability to create simple bookkeeping, allowing students to track their pocket money and financial inflows and outflows. Observations during the activities revealed that students were very enthusiastic and actively participated in every session. This program significantly enhanced students' understanding of basic financial literacy concepts and successfully encouraged positive changes in their attitudes and behaviors toward financial management.